Case Report: Targeted plasticity in spinal cord injury—the role of focal muscle vibration and neurocognitive rehabilitation in adaptative synaptic change along sensory and motor circuit - Filippo Camerota; Naomi Francesca Pocino; Federico Zangrando; Roberta Di Tommaso; Marco Paoloni; Massimiliano Mangone; Claudia Celletti (Frontiers in Rehabilitation Sciences)
PurposeThe purpose of this case was to investigate objectively and quantitatively the effects of the application of repeated focal muscle vibration (fMV) associated with neurocognitive exercise on a 46-year-old patient with spastic paraparesis secondary to the surgical removal of a C5–C6 ependymoma.MethodsWe have evaluated gait parameters, spasticity, and pain with clinical scales. We have applied focal muscle vibration on quadriceps femoris, hamstrings, gastrocnemius, and iliopsoas muscles bilaterally. A total of 30 sessions of fMV treatment of 80 min each was carried out over 30 consecutive days.ResultsAfter the whole treatment period, the patient showed an overall improvement in scores on the same assessment scales administered at admission. The gait analysis evaluation showed a reduction in stride time bilaterally, an increase in average walking speed, increased cadence, and a slight increase in step length.ConclusionThe improvements obtained have highlighted the relevance of the fMV application associated to physiotherapy in the field of neurological rehabilitation, particularly emphasizing the interest in increasing the number of sessions correlated with more durable clinical improvements over time. Results obtained have shown to persist for several months after discharge, allowing the patient to improve walking and to have greater autonomy in daily activities.